Impact assessment of IFPRI's research and related activities based on economywide modeling - Anderson, Kym (International Food Policy Research Institute, 2003)
Why is an economywide approach helpful for analyzing food policies, and what has been the impact of that part of IFPRI's activities over the past decade? This paper (the 21st in a series of studies commissioned by IFPRI to evaluate the impact of its research and related activities) attempts to assess the worth of those activities as part of a wider process aimed at improving the effectiveness of IFPRI's work and documenting for donors the wisdom of investing in it.... The report begins by laying out the utility of an economywide framework (Section 2), before summarizing the inputs into TMD's economywide modeling and other activities since 1994 (Section 3). It then catalogs the various outputs and tries to measure their outcomes in terms of such things as publication citations and website downloads of papers (Sections 4 and 5). The impact of those products is much more difficult to gauge (the standard attribution problem in assessing methodological and policy research), but two approaches are used in Section 6. One is to draw on responses to a questionnaire sent to a range of stakeholders in developing-country governments, policy think tanks, policy modelers, and other food and trade policy researchers at universities and international donor agencies. The other is to draw on narratives provided by current IFPRI staff and others. The final section summarizes what has been found in this assessment. -- from Author's Abstract